Answer:
A) y(t) = - 0.286e^(-9) + 1.287e^(-2)
Explanation:
A) M = 1kg
K = 18 N/m
by' = 11y'
So, using Newton's second law for the system, we obtain;
my" + by' + Ky = 0
So;
y" + 11y' + 18y = 0
The auxiliary equation of this is;
m² + 11m + 18 = 0
Solving for the roots to obtain, m = -9 and -2
So the general Solution is;
y(t) = C1 e^(-9) + C2 e^(-2)
and y'(t) = -9C1 e^(-2) - 2C2 e^(-2)
Now, from the question,
y(0) = 1 and y'(0) = 0
And so;
C1 + C2 = 1
And -9C1 - 2C2 = 0
Making C2 the subject in the second equation, we get;
C2 = - (9/2) = - 4.5C1
Putting - 4.5C1 for C2 in first equation to obtain;
C1 - 4.5C1 = 1
- 3.5C1 = 1
C1 = -(1/3.5) = -0.286
C2 = -4.5 x (-0.286) = 1.287
Thus equation of motion here is;
y(t) = - 0.286e^(-9) + 1.287e^(-2)